2023
DOI: 10.1111/mec.17095
|View full text |Cite
|
Sign up to set email alerts
|

Environmental microbes promote phenotypic plasticity in reproduction and sleep behaviour

Abstract: The microbiome has been hypothesized as a driving force of phenotypic variation in host organisms that is capable of extending metabolic processes, altering development and in some cases, conferring novel functions that are critical for survival. Only a few studies have directly shown a causal role for the environmental microbiome in altering host phenotypic features. To assess the extent to which environmental microbes induce variation in host life‐history traits and behaviour, we inoculated axenic Drosophila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Pathogenic and host-associated microorganisms, just as multicellular hosts, are part of a wider network of ecological interactions with environmental microbiota, which can affect host physiology. Environmental microbes serve as a source for the assembly of host-associated microbial communities ( Loudon et al, 2014 ; Smith et al, 2015 ; Knutie et al, 2017 ; Jani and Briggs, 2018 ; Prest et al, 2018 ; Callens et al, 2020 ; Singh et al, 2020 ; Téfit et al, 2023 ), which in turn have been repeatedly shown to affect host health and Darwinian fitness ( Shin et al, 2011 ; Fraune et al, 2015 ; Shreiner et al, 2015 ; Sison-Mangus et al, 2015 ; Knutie et al, 2017 ; Gould et al, 2018 ; Popkes and Valenzano, 2020 ; Weiland-Bräuer et al, 2020 ). Environmental microorganisms can also directly influence host physiology by affecting immune maturation early in life, with possible fitness consequences later ( Chen and Cadwell, 2022 ; Fallet et al, 2022 ; Walsh and Guillemin, 2022 ; Donald and Finlay, 2023 ; Fontaine and Kohl, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic and host-associated microorganisms, just as multicellular hosts, are part of a wider network of ecological interactions with environmental microbiota, which can affect host physiology. Environmental microbes serve as a source for the assembly of host-associated microbial communities ( Loudon et al, 2014 ; Smith et al, 2015 ; Knutie et al, 2017 ; Jani and Briggs, 2018 ; Prest et al, 2018 ; Callens et al, 2020 ; Singh et al, 2020 ; Téfit et al, 2023 ), which in turn have been repeatedly shown to affect host health and Darwinian fitness ( Shin et al, 2011 ; Fraune et al, 2015 ; Shreiner et al, 2015 ; Sison-Mangus et al, 2015 ; Knutie et al, 2017 ; Gould et al, 2018 ; Popkes and Valenzano, 2020 ; Weiland-Bräuer et al, 2020 ). Environmental microorganisms can also directly influence host physiology by affecting immune maturation early in life, with possible fitness consequences later ( Chen and Cadwell, 2022 ; Fallet et al, 2022 ; Walsh and Guillemin, 2022 ; Donald and Finlay, 2023 ; Fontaine and Kohl, 2023 ).…”
Section: Introductionmentioning
confidence: 99%